Multilinear Regression–Based Rock Physics Template Modeling for Sandstone Reservoir Characterization - Fahrizi, Muhammad Alif; Winardhi, Ignatius (Scientific Contributions Oil and Gas, 2026)
Rock Physics Templates (RPT) are widely used to link petrophysical parameters with elastic properties for fluid identification in reservoir characterization. Previous studies have demonstrated the potential of RPT for fluid detection method; however, well-defined procedures for determining rock matrix parameters and P-wave velocity (Vp) as the basis for RPT construction remain limited. This study develops a systematic workflow for RPT construction based on volumetric and rock physics approached, where rock matrix properties are estimated directly from wireline logs when core data is unavailable. The performance of the proposed RPT approach is evaluated through comparing with conventional elastic attribute methods, namely Curved Pseudo Elastic Impedance (CPEI) and Lambda–Rho analysis. The results indicate that the RPT workflow provides improved fluid discrimination than the conventional methods, highlithing its effectiveness as a reliable rock-physics-based tool for fluid identification in sandstone reservoirs.